Abiotic and biotic factors affecting recruitment variability of walleye pollock (Theragra chalcogramma) off the Pacific coast of Hokkaido, Japan. (22nd January 2013) - Funamoto, Tetsuichiro; Yamamura, Orio; Kono, Tokihiro; Hamatsu, Tomonori; Nishimura, Akira
Abstract Abiotic and biotic factors affecting the recruitment variability of the Japanese Pacific stock (JPS) of walleye pollock (Theragra chalcogramma) were examined using a bivariate regression and multivariate combined model. Of the abiotic variables around Funka Bay (spawning ground), February sea surface temperature (SST) and wind direction index showed significant bivariate relationships with recruitment. February SST was positively related to recruitment, suggesting that warmer water temperature in February favors JPS recruitment. On the other hand, the relationship between February wind direction index and recruitment predicts high JPS recruitment under predominant northwest winds in February. For the biotic variables in the Doto area (nursery ground), significant and negative bivariate relationships with recruitment were observed for catch per unit effort of Kamchatka flounder (Atheresthes evermanni), Pacific cod (Gadus macrocephalus), and walleye pollock, implying an important impact of predation by these groundfishes on JPS recruitment. The overall model incorporating these abiotic and biotic factors successfully reproduced the variability in JPS recruitment. Temperature and wind conditions around the spawning ground along with predator condition in the nursery ground appear to play a dominant role in the recruitment dynamics of JPS. Based on these results and prior knowledge, we propose a new hypothesis to explain the processes controlling JPS recruitment.